Modeling and Simulation of a Heat Recovery Steam Generator using Partially Known Design Point Data - Zewge, Mesfin G.; Lemma, T. A.; Ibrahim, A. A.; Sujan, D. (Trans Tech Publications Ltd, 2014)
In a cogeneration or combined heat and power plant, a heat recovery steam generator (HRSG) helps achieve overall thermal efficiency as high as 80%. The purpose of this study is to model and simulate the HRSG given partial design point data. The pinch and approach temperatures are optimized within generally accepted range. In order to satisfy the energy conservation equation, tuning parameters are used for the overall heat transfer coefficients corresponding to the evaporator and economizer. For the off-design simulation, the values of pinch and approach temperatures are adjusted until the modeling error is within a set limit. The effect of mass flow rate on the heat transfer coefficient is accounted for & by employing empirical relations. A 12 Ton/hr natural circulation HRSG was considered as a case study. The validation test on inlet temperatures of the exhaust gas and feed water to the economizer demonstrated relative percentage errors of 0.4246% and 1.8776%, respectively. The model can be used for fault detection and diagnostic system design, performance optimization, and environmental load assessment.